Awareness of the Differences Between Islamic Insurance and Conventional Insurance amongst Students of Islamic Studies in Sri Lanka - Mohamed Minaz, Mohamed Naushad; Mohamed Mazahir, Sayed Mohamed; Fathima Nihla, Ahamed Mukthar Faiser; Fathima Masliha, Kalanthar Lebbe (Invest Journal of Sharia & Economic Law, 2023)
This study investigates Takaful, an Islamic insurance model, as a viable alternative to conventional insurance. It identifies the issue of insufficient awareness and understanding of Takaful among Sri Lankans despite its increasing popularity in the region. This study aimed to assess the level of awareness and acceptance of Takaful and identify the factors influencing these aspects. The research methodology involved a survey of Sri Lankan consumers, with data collected through questionnaires. The findings indicate that although there is a rising demand for Takaful in Sri Lanka, a significant number of individuals remain either unaware of it or are hesitant to utilize it due to misconceptions. The study suggests that enhancing awareness and comprehension of Takaful could foster greater participation in this form of insurance in Malaysia. Future research should investigate the reasons for the lack of engagement with Takaful and explore strategies to promote insurance literacy and engagement.